Implementasi Pembelajaran Online dalam Meningkatkan Pemahaman Siswa di Masa Pandemi Covid-19 - Silmi Yassifi Maspupah; Eka Naelia Rahmah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
The Covid-19 pandemic has had a fairly large impact, one of which is in the world of education, so the government issued a policy for the implementation of online learning, this is a big challenge for educators so that students can understand learning even by carrying out online learning. This study uses qualitative research, using observation, interviews, and documentation methods, and using data analysis, namely data reduction, data presentation, and drawing conclusions.The results of this study indicate that the implementation of online learning in improving students' understanding of PAI subjects during the covid-19 pandemic. Its implementation it is in accordance with the plans that have been made by teachers such as lesson plans, syllabus, annual programs, and has used methods, strategies and media adapted to students, although there are obstacles but during learning Islamic Religious Education there is no decrease in learning outcomes or a decrease in student grades, the average score of students is 80 both in offline learning and in online learning.